ASUHAN KEPERAWATAN PADA PASIEN DENGAN POST OPERATIF HERNIA INGUINALIS : STUDI KASUS - Afdhal Muchtar; Roma Sitio; Yeni Rimadeni; Naylul Muna (JOURNAL KEPERAWATAN, 2022)
Inguinal hernia is defined as a lump of an organ through the inguinal cleft in the abdominal wall. According to the World Health Organization (WHO), in 2010-2015 hernia patients reached nearly 20 million cases and there were 20 million cases of inguinal hernia surgery every year. In Indonesia, it is estimated that there are 300 thousand cases. Based on data obtained from the HCU Room at RSUD Dr. Zainoel Abidin Banda Aceh, from January 2020 to April 2021, there were 14 cases. The purpose of this study was to determine the implementation of nursing care for Mrs. T with postoperative inguinal hernia in the HCU Room of Dr. Zainoel Abidin Hospital Banda Aceh in 2021. In compiling this case study the author uses a descriptive method with a nursing process approach which includes assessment, nursing diagnoses, nursing planning, implementation and evaluation. The results of nursing care were obtained after 3x24 hours the client's pain complaints decreased from a scale of 6 to 4, respiratory status was 18 x/m, daily activities were still assisted. Based on the results of the final evaluation, it was concluded that Mrs. T's problem was partially resolved for the diagnosis of acute pain and activity intolerance. As for the ineffective breathing pattern, the problem is resolved. The suggestions given are expected to improve communication and obtain more accurate data, so that nursing care can be carried out appropriately.